E-Module Social Studies Containing Balinese Folk Tales Based on Pancasila Student Profiles for Grade V Students in Elementary Schools - Sinta Dewi, Ida Ayu Agung Paramita; I Gusti Agung Ayu Wulandari; Didith Pramunditya Ambara (Universitas Pendidikan Ganesha, 2024)
This study was motivated by the low interest and motivation of elementary school students in learning Social Studies (IPS), which is largely due to the limited variety of instructional media and reliance on textbooks. The main objective of this research is to develop and examine the feasibility and effectiveness of a Social Studies e-module incorporating Balinese folktales based on the Pancasila Student Profile to enhance the competence and learning interest of fifth-grade students. This research employed a Research and Development (R&D) design using the Dick and Carey model. The study involved 58 fifth-grade students, divided into a control group (VA) and an experimental group (VB). Data were collected through tests, questionnaires, and expert validations using instruments such as validation sheets, learning outcome tests, and student response questionnaires. Data analysis was conducted using both descriptive (qualitative and quantitative) and inferential statistical methods. The results showed that the developed e-module was highly feasible, with validation scores of 92% (content expert), 95% (media expert), 95% (language expert), 94.16% (individual trials), and 90% (small group trials). The effectiveness test indicated a significant difference between the experimental and control groups (significance value < 0.05). The findings conclude that the e-module integrating Balinese folktales and the Pancasila Student Profile is effective in improving students’ competence and interest in Social Studies learning. The implication of this study underscores the importance of incorporating contextual, character-based local